2015
DOI: 10.3390/cryst5010154
|View full text |Cite
|
Sign up to set email alerts
|

Let’s Talk about MOFs—Topology and Terminology of Metal-Organic Frameworks and Why We Need Them

Abstract: Recent IUPAC (The International Union for Pure and Applied Chemistry) recommendations on the terminology of metal-organic frameworks are reviewed and the background to a proposed topology classification is discussed. The various numerical designators such as point symbols, vertex symbols and transitivity are also explained and their importance elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 26 publications
0
33
0
1
Order By: Relevance
“…Alternatively, this may mean that if the scientific terminologies developed so far to serve some specific purposes are muddled, then one has left with no choice to separate out, for instance, which are inorganic, which are organic, which are noncovalent, and which are organometallic chemistry, and what are the similarities and differences between them. This view is not very unusual since terminology deals with all technical vocabulary excluding names of individual compounds …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, this may mean that if the scientific terminologies developed so far to serve some specific purposes are muddled, then one has left with no choice to separate out, for instance, which are inorganic, which are organic, which are noncovalent, and which are organometallic chemistry, and what are the similarities and differences between them. This view is not very unusual since terminology deals with all technical vocabulary excluding names of individual compounds …”
Section: Discussionmentioning
confidence: 99%
“…In these, the authors have provided the physical significance and chemical relevance of why should one name a bond with a name. Similarly as above, Öhrström has discussed his opinion on the controversy that lies between metal‐organic framework and coordination polymer in his article entitled ‘Let's talk about MOFs–topology and terminology of metal‐organic frameworks and why we need them’; the reader may find the above articles as interesting reads.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, by reaction of 1 ⋅2 EtOH with AgClO 4 we obtained {[Fe 4 (pPy) 2 (dpm) 6 ] 2 Ag}(ClO 4 ) ( 2 ), a 3D metal–organic framework (MOF) crystallizing in a cubic space group. Its crystal structure consists of two interlocked dia networks, according to IUPAC nomenclature, with silver(I) ions as the tetrahedral nodes coordinated by four pyridyl nitrogen atoms of Fe 4 complexes. By performing magnetic measurements and W‐band ( ν ≈94 GHz) EPR spectroscopy we found that the Fe 4 units retain the same magnetic behaviour as in 1 ⋅2 EtOH.…”
Section: Introductionmentioning
confidence: 99%
“…Controlling network interpenetration. Interpenetration, where the empty space described by the crystalline framework accommodates one or more additional networks 94 and which can adversely affect pore volume and impact internal surface area 95 , is another aspect of 3D COFs that requires improved understanding and synthetic control. Whereas interpenetration in 3D COFs has typically been determined by structural modeling and unit-cell indexing and is reported as an inherent characteristic, efforts to better understand, characterize, and even modify degrees of interpenetration have been recently reported.…”
Section: Review Articlementioning
confidence: 99%